Developmental dysplasia of the hip: A computational biomechanical model of the path of least energy for closed reduction. Issue 8 (8th November 2016) - Zwawi, Mohammed A.; Moslehy, Faissal A.; Rose, Christopher; Huayamave, Victor; Kassab, Alain J.; Divo, Eduardo; Jones, Brendan J.; Price, Charles T.
ABSTRACT: This study utilized a computational biomechanical model and applied the least energy path principle to investigate two pathways for closed reduction of high grade infantile hip dislocation. The principle of least energy when applied to moving the femoral head from an initial to a final position considers all possible paths that connect them and identifies the path of least resistance. Clinical reports of severe hip dysplasia have concluded that reduction of the femoral head into the acetabulum may occur by a direct pathway over the posterior rim of the acetabulum when using the Pavlik harness, or by an indirect pathway with reduction through the acetabular notch when using the modified Hoffman–Daimler method. This computational study also compared the energy requirements for both pathways. The anatomical and muscular aspects of the model were derived using a combination of MRI and OpenSim data. Results of this study indicate that the path of least energy closely approximates the indirect pathway of the modified Hoffman–Daimler method. The direct pathway over the posterior rim of the acetabulum required more energy for reduction. This biomechanical analysis confirms the clinical observations of the two pathways for closed reduction of severe hip dysplasia. The path of least energy closely approximated the modified Hoffman–Daimler method. Further study of the modified Hoffman–Daimler method for reduction of severe hip dysplasia may be warranted based on this computational biomechanical analysis. © 2016 The Authors. Journal of Orthopaedic Research Published by Wiley Periodicals, Inc. on behalf of Orthopaedic Research Society. J Orthop Res 35:1799–1805, 2017. Abstract : Clinical reports of severe hip dysplasia have concluded that reduction of the femoral head into the acetabulum may occur by a direct pathway over the posterior rim of the acetabulum, or by an indirect pathway with reduction through the acetabular notch. Results of this study indicate that the path of least energy closely approximates the indirect pathway of the modified Hoffman–Daimler method. Further study of the modified Hoffman–Daimler method for reduction of hip dysplasia may be warranted.